Desain Ulang Balok dan Kolom Komposit - Syafridal Is; Muhammad Zardi; Nanda Mahathir (Jurnal Teknik Sipil Unaya, 2019)
The aim of this study is to redesign the beams and columns of reinforced concrete into a composite structure of Women's Empowerment and Child Protection Agency to derive a comparison of strength and efficiency between concrete-steel composite structures and reinforced concrete structures without changing the layout of columns and beams in the initial planning. LRFD (Load Resistance Factor Design) method and SAP2000 ver.14 as a tool were used in this study. The design was based on Indonesian Standard Regulation. The concrete strength (f’c) and steel strength ( were25 MPa and 250 MPa, respectively. In this study, steel profile BJ 37of WF (400 x 400 x 21 x 21) mm was used for beam and WF (400 x 400x 30 x 50) mm with concrete cross section (500 x 500) mm for column. The results of redesign composite structure for three-story building with the designed steel profile is fulfilled the strength requirements. The obtained maximum moment of beam and column are 36789,36 kg.cm and 43942,2 kg.cm, respectively. The used of composite material is 76,925% more expensive than reinforced concrete material.